THE IMPACT OF DIGITAL COMMUNICATION ON HUMAN RELATIONSHIPS AND MENTAL HEALTH - Aggelopoulou, Ifigenia; Mavrogianni, Christina (Open Schools Journal for Open Science, 2025)
Digital communication has profoundly altered how humans connect, communicate, and maintain relationships. While technologies such as social media, instant messaging, and video calls offer convenience and global accessibility, they also introduce challenges to mental health and emotional well-being. This report explores both the positive and negative consequences of digital communication on interpersonal relationships, with a focus on mental health.